Advances in bioceramics and porous ceramics VII a collection of papers presented at the 38th International Conference on Advanced Ceramics and Composites, January 27-31, 2014, Daytona Beach, Florida - Narayan, Roger (John Wiley & Sons, 2015)
A collection of 15 papers from The American Ceramic Society's 38th International Conference on Advanced Ceramics and Composites, held in Daytona Beach, Florida, January 26-31, 2014. This issue includes papers presented in Symposium 5 - Next Generation Bioceramics and Biocomposites and Symposium 9 - Porous Ceramics: Novel Developments and Applications
Includes bibliographical references and index
Keywords: Conference papers and proceedings / fast / (OCoLC)fst01423772; HEALTH & FITNESS / Holism / bisacsh; HEALTH & FITNESS / Reference / bisacsh; MEDICAL / Alternative Medicine / bisacsh; MEDICAL / Atlases / bisacsh; MEDICAL / Essays / bisacsh; MEDICAL / Family & General Practice / bisacsh; MEDICAL / Holistic Medicine / bisacsh; MEDICAL / Osteopathy / bisacsh; Biomedical materials / fast / (OCoLC)fst00832586; Ceramic materials / fast / (OCoLC)fst00850974; Ceramics in medicine / fast / (OCoLC)fst00851134; Porous materials / fast / (OCoLC)fst01071907; Ceramic materials / Congresses; Porous materials / Congresses; Ceramics in medicine / Congresses; Biomedical materials / Congresses